Effects of endoplasmic reticulum stress on the expression of inflammatory cytokines in patients with ulcerative colitis - Li, Nan; Wang, Xue-Ming; Jiang, Li-Jun; Zhang, Meng; Li, Na; Wei, Zhen-Zhen; Zheng, Nan; Zhao, Ya-Jiao (World journal of gastroenterology : WJG, 2016)
To explore the changes of X-box binding protein 1 splicing (XBP1s) and inflammatory cytokine expression in patients with ulcerative colitis (UC) in response to endoplasmic reticulum stress (ERS). Reverse transcription polymerase chain reaction and quantitative polymerase chain reaction were performed to detect the forms of XBP1s and the expression of interleukin (IL)-2, interferon (IFN)-γ, and IL-17α. Differences between patients with UC and normal subjects were then determined. Mononuclear cells of the peripheral blood of normal subjects and UC patients with were stimulated with no drugs (control), phytohemagglutinin (PHA), thapsigargin (TG), or both PHA and TG. XBP1s in patients with UC exhibited splicing, which was greater with co-stimulation than single stimulation. Co-stimulation increased the expression level of IL-2, IFN-γ, and IL-17α. The T lymphocytes of both normal subjects and patients with UC responded to ERS by activating the XBP1s-mediated signalling pathway, upregulating the expression of inflammatory cytokines, and increasing the occurrence of inflammation. The mononuclear cells in the peripheral blood of patients with UC were more sensitive to ERS than those in the peripheral blood of normal subjects.